Efficacy and safety of XELOX combined with anlotinib and penpulimab vs XELOX as an adjuvant therapy for ctDNA-positive gastric and gastroesophageal junction adenocarcinoma: a protocol for a randomized, controlled, multicenter phase II clinical trial (EXPLORING study) - Chen, Yizhang; Zhang, Jiaguang; Han, Gaohua; Tang, Jie; Guo, Fen; Li, Wei; Xie, Li; Xu, Hao; Zhang, Xinyi; Tian, Yitong; Pan, Lanlan; Shu, Yongqian; et al. (Frontiers in Immunology, 2023)
Background The efficacy of current adjuvant chemotherapy for gastric adenocarcinoma/gastroesophageal junction adenocarcinoma (GA/GEJA) leaves much to be desired. ctDNA could serve as a potential marker to identify patients who are at higher risk of recurrence. Reinforcing standard adjuvant chemotherapy with immunotherapy has already been indicated to significantly improve clinical outcome, albeit such evidence is rare in GA/GEJA. Here, we intend to explore the clinical benefit of the reinforcement of adjuvant immunotherapy and antiangiogenics alongside with chemotherapy in patients who are deemed in high risk of recurrence by ctDNA analysis, which might shed light on further improvements in adjuvant therapy for GA/GEJA. Methods/Design This study is designed as a prospective, multicenter, randomized, controlled phase II study in patients histologically or cytologically diagnosed with GA/GEJA who underwent D2 gastrectomy and achieved R0 or R1 resection. From February 2022, a total of 300 stage III patients will be enrolled and subjected according to ctDNA sequencing results, and those with positive results will subsequently be randomized 1:1 to arm A or B. Patients in arm A will receive anlotinib, penpulimab and XELOX for 6-8 cycles, maintained with anlotinib and penpulimab for up to 1 year, while patients in arm B will receive XELOX alone for 6-8 cycles. ctDNA-negative patients will be assigned to arm C, and patients who are ctDNA positive but failed in randomization will be assigned to arm D. Patients in arms C and D will receive the investigator’s choice of therapy. The primary endpoint is the median disease-free survival (DFS) of arm A versus arm B determined via CT/MRI imaging. Secondary endpoints include the DFS of ctDNA positive patients versus ctDNA negative patients, the 2- and 3-year DFS rates, overall survival (OS), the impact of hallmark molecules on the treatment response, adverse events (AEs), and the impact of nutrition status or exercise on recurrence. Discussion We expect that ctDNA would be a strong prognostic factor and ctDNA-positive patients are at higher risk of relapse than ctDNA-negative patients. The addition of anlotinib and penpulimab to XELOX, may contribute to delaying relapse in ctDNA-positive patients. Trial registration https://www.clinicaltrials.gov, identifier NCT05494060.